2006
DOI: 10.1186/gb-2006-7-8-r76
|View full text |Cite
|
Sign up to set email alerts
|

Integration of metabolite with transcript and enzyme activity profiling during diurnal cycles in Arabidopsisrosettes

Abstract: Arabidopsis diurnal cycles

An analysis of the temporal dynamics of metabolite and transcript levels, as well as enzyme activity, of 137 metabolites during diurnal cycles in Arabidopsis leaves

Abstract Background: Genome-wide transcript profiling and analyses of enzyme activities from central carbon and nitrogen metabolism show that transcript levels undergo marked and rapid changes during diurnal cycles and after transfer to darkness, whereas changes in activities are smaller and delayed. In th…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(141 citation statements)
references
References 63 publications
11
127
1
2
Order By: Relevance
“…Osuna et al [19] reported changes in transcript levels for >1,700 genes after 3 h of 15 mM sucrose addition to Arabidopsis plants. A comprehensive analysis revealed radical changes at the metabolic, proteomic, and overall transcriptional levels during a circadian cycle and extended night in wild-type Arabidopsis plants and starchless pgm mutant [19, 22, 23]. Bläsing et al [20] showed that more than 17% of the genes presented more than a two-fold larger diurnal change in the starchless pgm mutant when compared with Col-0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osuna et al [19] reported changes in transcript levels for >1,700 genes after 3 h of 15 mM sucrose addition to Arabidopsis plants. A comprehensive analysis revealed radical changes at the metabolic, proteomic, and overall transcriptional levels during a circadian cycle and extended night in wild-type Arabidopsis plants and starchless pgm mutant [19, 22, 23]. Bläsing et al [20] showed that more than 17% of the genes presented more than a two-fold larger diurnal change in the starchless pgm mutant when compared with Col-0.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of genes showed significant transcript changes in Arabidopsis starchless mutants lacking the chloroplastic isoform of phosphoglucomutase (PGM) gene when compared with wild-type plants at different time-points during diurnal light/dark cycles [19, 22, 23]. Nevertheless, little is known about the proteome profiling in plant carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples concerning the iron transporter IRT1 (57), the high-affinity NO 3 Ϫ transporter from Tuber borchii (58), the sulfate transporter HVST1 from barley (59), the phosphate transporter PT1 from Medicago and tomato (60,61), and aquaporines (62) all showed a correlation between the level of mRNA and the level of the protein in response to iron starvation, nitrogen availability, sulfate re-supply, phosphate starvation, and salinity, respectively. However, recent large-scale experiments showed that transcript levels undergo marked and rapid changes during diurnal cycles and after transfer to darkness, whereas changes in enzyme activities are smaller and delayed (63). This strongly suggests that in many cases additional regulation at the level of protein is required.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting energy deprivation was suggested to be common to most types of stress and to trigger specific responses (Baena-González and Sheen, 2008), leading to the massive alteration of cellular processes, referred to as LES. This includes growth arrest and metabolic reprogramming, comprising the repression of biosynthetic activities and sugar storage, as well as the induction of catabolic processes, photosynthesis, and sugar remobilization (Paul and Pellny, 2003; Gibon et al, 2006). In addition, the expression of thousands of genes is altered (Usadel et al, 2008).…”
Section: The Low Energy Syndrome Is Part Of Stress Adaptationmentioning
confidence: 99%